GEOPOLITICA ȚĂRILOR MICI ȘI MASS-MEDIA. REPUBLICA MOLDOVA - Lescu, Mihai (CEP USM, 2024)
Today the world is becoming more and more complex. The (geo)political and geostrategic environment is turbulent and marked by big or small actors (states, continental/transnational economic structures or intergovernmental organizations, and, not least, media institutions), which determine the dynamics of national and international life. In the article the author discusses the interaction between the geopolitics of small countries and the mass media. He mentions that small countries and their media should be treated with caution and a lot of attention when discussing geopolitics, because recently they have become the epicenter of events that attract the attention of global public opinion. The advantages of media geopolitics, including those of small countries, are increasingly felt in the context of the rapid development of communication and information technologies. This fact is also reflected in the activity of the mass media in the Republic of Moldova, which also has certain geopolitical interests in the region of its location. In conclusion, the author comes with recommendations regarding the strategies and tactics to be applied by the Moldovan mass media in the process of debating geopolitical issues
GEOPOLITICS OF SMALL COUNTRIES AND MASS-MEDIA. REPUBLIC OF MOLDOVA
LESCU, Mihai. Geopolitica țărilor mici și mass-media. Republica Moldova. În: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Științe umanistice și sociale, 9-10 noiembrie 2023. CEP USM, 2024, pp. 326-332. ISBN 978-9975-62-691-0 (PDF).
Keywords: mass media; geopolitics; strategic interest; audiovisual; written press